2013
DOI: 10.1007/s40121-013-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis, Anti-Tumor Necrosis Factor Therapy, and Tuberculosis: Report of Three Challenging Cases and Literature Review

Abstract: IntroductionThe era of biologic therapies has provided new options for the treatment of chronic plaque psoriasis. However, safety concerns have led to intensive screening and monitoring of patients receiving anti-tumor necrosis factor alpha (anti-TNF-alpha) agents.MethodsThe authors describe the cases of three patients with moderate to severe psoriasis treated with anti-TNF agents, with challenging diagnostic and treatment aspects regarding tuberculosis (TB) infection, a serious adverse event associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…The former was consistent with the systematic meta‐analyses comprising either randomized clinical trials or registries/cohort studies of anti‐TNF‐α drugs that reported significant TB risk increment in RA patients . On the other hand, detection of increased significant TB risk for PsA, albeit with a quite broad confidence interval, could be regarded as the first in the literature except few suspected case reports . Furthermore, a small cohort of PsA patients with latent TB infection reported no development of TB during 2‐year follow‐up .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The former was consistent with the systematic meta‐analyses comprising either randomized clinical trials or registries/cohort studies of anti‐TNF‐α drugs that reported significant TB risk increment in RA patients . On the other hand, detection of increased significant TB risk for PsA, albeit with a quite broad confidence interval, could be regarded as the first in the literature except few suspected case reports . Furthermore, a small cohort of PsA patients with latent TB infection reported no development of TB during 2‐year follow‐up .…”
Section: Resultssupporting
confidence: 84%
“…13,30 On the other hand, detection of increased significant TB risk for PsA, albeit with a quite broad confidence interval, could be regarded as the first in the literature except few suspected case reports. 34 Furthermore, a small cohort of PsA patients with latent TB infection reported no development of TB during 2-year follow-up. 35 Considering probable overdiagnosis of latent TB infection and consequent prophylaxis due to overestimation of tuberculin skin test values among psoriasis patients, 36,37 the risk observed in our PsA patients might be raised more than predicted.…”
Section: Discussionmentioning
confidence: 99%
“…( 3 , 4 ). Over the past 20 years, therapy with biologics has resulted in significant responses, but immune depression remains a challenge ( 5 ).…”
mentioning
confidence: 99%
“…Cases of disseminated or military tuberculosis, a disease caused by the acid-fast bacillus M. tuberculosis , secondary to TNF-α inhibitors are becoming more commonplace, though they remain rare in paediatric patients. 4–8 However, the increasing use of immunomodulatory medications such as TNF-α inhibitors is increasing the risk of presentation. Testing for latent tuberculosis remains imperative prior to initiating immunomodulatory therapy, but it is unable to prevent all infections.…”
Section: Discussionmentioning
confidence: 99%